A 10-year retrospective study of free anterolateral thigh flap application in 872 head and neck tumour cases. Issue 9 (September 2015) - Xu, Z.; Zhao, X.P.; Yan, T.L.; Wang, M.; Wang, L.; Wu, H.J.; Shang, Z.J.
Abstract The aim of this study was to report the clinical features, reliability, and various applications of free anterolateral thigh (ALT) flaps and to provide a 10-year retrospective review of the application of this flap in head and neck tumour patients. A retrospective study was performed of 872 patients who underwent immediate reconstruction of head and neck tumour-induced defects with ALT flaps between April 2005 and April 2014. The study sample consisted of 609 males and 263 females aged 18–79 years. The shapes and sizes of the flaps were designed individually to meet various demands of reconstruction in the head and neck region. The overall rate of successful reconstruction was 97.4%. The reasons for 57 cases of flap compromise were analyzed. The time to detection of flap crisis was often within the first 8 h after surgery (64.9%). One- and two-vein anastomosis strategies in microsurgery were compared, and significant differences were observed in terms of the time to detection of flap compromise and the rate of successful flap salvage. In conclusion, the free ALT flap provides unique features for the reconstruction of oral and facial defects in a reliable and versatile approach. The ALT flap is a favourable and versatile 'workhorse' flap for head and neck reconstruction.